Patients of COVID-19 may benefit from sustained Lopinavir-combined regimen and the increase of Eosinophil may predict the outcome of COVID-19 progression. (June 2020) - Liu, Fang; Xu, Aifang; Zhang, Yan; Xuan, Weiling; Yan, Tingbo; Pan, Kenv; Yu, Wenyan; Zhang, Jun
Highlights: An asymptomatic 2019-coronavirus disease patient with normal radiography throughout appeared in this study. Lopinavir has a positive effect on 2019-coronavirus disease patients. Eosinophil counts presented potentiality as a predictor on the progression of 2019-coronavirus disease. Abstract: Objectives: To explore the epidemiological information, clinical characteristics, therapeutic outcomes and temporal progression of laboratory findings in 2019-coronavirus disease (COVID-19) patients exposed to lopinavir. Methods: We collected data from ten COVID-19 patients admitted between January 22, 2020 and February 11, 2020 at Xixi hospital in Hangzhou, China. Results: Of ten patients, secondary, tertiary and quartus patients emerged; the incubation period was 3–7 days. Mainly initial symptoms were cough and low fever (37.3–38.0 °C). An asymptomatic case presented normal radiography, the others had ground glass opacities. All cases (three transferred, seven discharged) were exposed to lopinavir on initial hospitalization. Three patients stopped lopinavir because of adverse effects, two of them deteriorated, one was hospitalized longer than others who with sustained lopinavir use. Levels of potassium, albumin, and lymphocytes were low, but increased persistently after treatment. Eosinophil values were low on initial hospitalization, then all returned to normal before discharge. Viral load of SARS-CoV-2, radiography and eosinophil improved continuously in 3–14, 6–8 and 7–9 days, respectively. Conclusions: Increasing eosinophils may be an indicator of COVID-19 improvement. The COVID-19 patients may benefit from sustained lopinavir use. More research on a larger scale is needed to verify these points.